Sodium Arsenite Induced Systemic Organ Damage and Changes in Various Blood Parameters in Mice (Dhaka University Journal of Pharmaceutical Sciences, 2013)
In this study, we examined the toxic effects of arsenic in vivo taking mice as a model animal. Swiss albino mice with similar weights were divided into two groups. The mice belonging to the first group were used as the control, while the other group was exposed to sodium arsenite (SA) through drinking water. Compared to control, the level of hemoglobin in SA-exposed mice was decreased while the number of neutrophils and monocytes were increased. In addition, SA also induced increase in liver and spleen weight within 8 weeks of exposure. In contrast, the weight of the kidney was found to decrease. These findings in mice model might be useful for better understanding of the toxic effects of arsenic in order to develop effective remediation process against arsenicmediated effects on human health. DOI: http://dx.doi.org/10.3329/dujps.v11i2.14576 Dhaka Univ. J. Pharm. Sci. 11(2): 169-172, 2012 (December)